Rethinking Youth Resilience in Africa: The Untapped Role of Intergenerational Care and Indigenous Support Systems in Community Health - Velisiwe Gasa; Moses Mhide Kpum (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: Global health narratives on youth resilience predominantly reflect Western-centric models emphasizing individual agency and nuclear family structures, marginalizing the intergenerational care networks and indigenous knowledge systems central to African societies. Objective: This conceptual paper critically examines the limitations of Western resilience frameworks in African contexts and proposes a reconceptualization grounding youth resilience in indigenous epistemologies, particularly Ubuntu philosophy and intergenerational care practices. Methods: Drawing on decolonial theory, African-centered psychology, and community resilience literature, we synthesize evidence from ethnographic studies, program evaluations, and regional health data across sub-Saharan Africa to demonstrate the efficacy of culturally grounded approaches. Results: Indigenous support systems, including grandparent-headed households, traditional healing practices, and community-based care networks, constitute tested resilience mechanisms that have sustained African youth through adversity yet remain systematically undervalued. Successful integration models from South Africa, Senegal, and Uganda demonstrate superior outcomes when indigenous wisdom informs youth development programming. Conclusion: Repositioning intergenerational care and indigenous knowledge from peripheral supplements to foundational pillars requires substantial policy reform, culturally appropriate research methodologies, and deliberate decolonization of health and social service systems across Africa.